Application of Breast Care to Fulfill the Pain Comfort in Post Partum Mothers with Swollen Breasts - Elis Roslianti; Ade Fitriani; Rosmalina Hoerunisa (Jurnal Vocational Nursing Sciences (VNUS), 2022)
Objective: The purpose of this study was to provide postpartum health care through breastfeeding (ASI) to increase milk production for mothers after giving birth. Method: The method used is descriptive and based on a case study approach. with the random sampling technique. The sample elements examined in this case study were postpartum patients with inefficient breastfeeding problems, using data collection techniques such as interviews, observations, physical examinations, and documentation studies. Result: The findings of the study indicated that the diagnosis was established, namely that breastfeeding was not successful due to insufficient milk supply. Procedures and procedures are breast care or breast care to improve blood flow and prevent blockage of the milk ducts to facilitate milk production. Conclusion: Maternity care for postpartum clients with ineffective breastfeeding problems is an insurmountable problem. As a result, after 3 days of undergoing breast care, the patient breastfeeds quite profusely.